STUDI ANALISIS KOEFISIEN ABSORBSI PAPAN AKUSTIK PADA KETEBALAN BERVARIASI BERBAHAN DASAR LIMBAH KULIT JAGUNG DAN SABUT KELAPA (SOLUSI ALTERNATIF RAMAH LINGKUNGAN) - Said L, Muh.; Nurmin, Nurmin; Zelviani, Sri (JFT: Jurnal Fisika dan Terapannya, 2020)
This study aims to detemine the effect of thickness on the absorption coefficient of acoustic boards from corn waste and coconut fiber with polyester resin adhesive. The procedure used is used in the research carried out by making acoustic boards with two types of samples, which are fine chopped materials and materials that have been roughly cut with a thickness of 0.7 cm, 1.0 cm and 1.5 cm and measure the coefficient absorption of the thickness of the acoustic material board. The frequency value used is 200 Hz, 250 Hz, 500Hz, 1000 Hz, 2000 Hz and also 4000 Hz. Based on the results of research conducted, it is found that the absorption coefficient value of straight-line coefficient, where the thicker a material, the smaller the coefficient of absorption. Sound absorption coefficient is good, namely at all thicknesses with a frequency of 200 Hz, 250 Hz and 500 Hz both from fine counts and rough counts. This shows that acoustic boards made of corn husk and coconut fiber can be used as sound absorbers because they have been included in the requirements of the ISO 11654 standard.